Level of Importance and Consumer Satisfaction Analysis of Carica Strudel Products - Astuti, Santi Dwi; Ayuningtyas, Laksmi Putri; Dewi, Ervina Mela; Haryanti, Pepita; Ardita, Andreas Dimas Fajar (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
Carica has now become a typical commodity of Wonosobo Regency. One of the Micro, Small and Medium Enterprises (MSMEs) engaged in carica processing in Wonosobo Regency is the Berkah Mandiri Joint Business Group (KUB). One of its products is carica strudel. Carica strudel is a food product in the form of a multi-layered pastry that is rolled and then filled with cooked carica fruit to form a fla-like shape. Strudel carica has been produced and distributed since 2021. Promotional activities carried out by strudel carica producers have not been maximized. This must be improved in order to increase business turnover. The purpose of this study is to determine recommendations for attribute strategies that need to be improved so that they can increase business turnover. This study used 100 respondents with the criteria that are at least 17 years old and have consumed strudel carica at least 2 times in the last 3 months. The aspects studied include pastry skin, strudel filling, packaging, and price & promos. The methods used to measure the level of importance and customer satisfaction are Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that each aspect has attributes with the highest level of importance, satisfaction, and suitability. The IPA matrix shows that there are 11 superior attributes of carica strudel, namely softness of the skin, comparison of skin to filling, chewiness, crispness, flavor, sweetness, size, sweetness of fla, packaging shape, ease of opening the package, and price compatibility with quality. There are 7 attributes recommended for improvement, namely the aroma of the skin, the savory taste of the skin, the sour taste of the fla, the type of packaging material, label design, completeness of label information, and promotion methods through social media. Based on the CSI method, a consumer satisfaction index value is obtained in the satisfied category.